2017
DOI: 10.1093/bioinformatics/btx679
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility prediction via a hybrid deep convolutional neural network

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Furthermore, the underlying sequence features of these peaks were extracted using neural networks and were shown to recapitulate known TF motifs. This confirmed that TFs play an important role in gene regulation through open, accessible chromatin [78,79]. Fine tuning of parameters is essential for all aforementioned tools [9,33], as the width of open chromatin varies Signal tracks are generated from BAM file (Raw) and bias corrected by HINT-ATAC (Bias corrected).…”
Section: Core Analysis: Peak Callingmentioning
confidence: 71%
“…Furthermore, the underlying sequence features of these peaks were extracted using neural networks and were shown to recapitulate known TF motifs. This confirmed that TFs play an important role in gene regulation through open, accessible chromatin [78,79]. Fine tuning of parameters is essential for all aforementioned tools [9,33], as the width of open chromatin varies Signal tracks are generated from BAM file (Raw) and bias corrected by HINT-ATAC (Bias corrected).…”
Section: Core Analysis: Peak Callingmentioning
confidence: 71%
“…And it is very meaningful to explain biological meaning in the process of training of CNN with visualization. Recently, many studies on biological computing prediction classifications Li et al 2017a;Liu et al 2017c;Zeng et al 2018) involving CNNs have used convolution kernels of the first layer to extract informative motifs from massive sequence data sets. These followed on from the heuristic work from Deepbind (Alipanahi et al 2015) that generated a position weight matrix (PWM) by aligning all matched sequence segments and calculating the frequency for each kernel.…”
Section: Learned and Analyzed Motifs From Cnn Kernelmentioning
confidence: 99%
“…In the recent years, CNNs have been successfully used in a wide spectrum of fields such as computer vision (Razavian, et al, 2014) and natural language processing (Vinyals, et al, 2015). In bioinformatics, CNNs have been used to predict regulatory elements , chromatin accessibility (Liu, et al, 2018) and epigenetic states of a DNA fragment Zhou and Troyanskaya, 2015) , as well as explain functional implications of genetic variants (Zhou and Troyanskaya, 2015).…”
Section: Introductionmentioning
confidence: 99%